2020
DOI: 10.2147/dmso.s248948
|View full text |Cite
|
Sign up to set email alerts
|

<p>microRNA Expression Profiles in Myocardium of High-Fat Diet-Induced Obesity Rat</p>

Abstract: A high-fat diet (HFD) can lead to cardiac dysfunction, hypertrophy, and fibrosis. This study aimed to explore microRNA expression profiles in the myocardium of HFDinduced obesity rat. Materials and Methods: Wistar rats were randomly divided into two groups, and fed with normal chow diet (NCD) or HFD for 20 weeks. Cardiac function was evaluated by echocardiography. Left ventricular myocardium was harvested to assess the extent of myocardial morphology alteration. MicroRNA expression was analyzed using Agilent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
(30 reference statements)
0
10
0
1
Order By: Relevance
“…After 8 weeks of HFD, we observed alterations in cardiac morphology indicative of the development of concentric hypertrophy, which was also prominently present after 12 weeks. Cardiac hypertrophy often precedes the development of heart failure [ 38 ], and it is known that a prolonged HFD regime (>20 weeks) additionally results in decreased cardiac function [ 39 , 40 ]. Hence, the rats at 12 weeks of HFD are on a one-way road towards lipid-induced cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…After 8 weeks of HFD, we observed alterations in cardiac morphology indicative of the development of concentric hypertrophy, which was also prominently present after 12 weeks. Cardiac hypertrophy often precedes the development of heart failure [ 38 ], and it is known that a prolonged HFD regime (>20 weeks) additionally results in decreased cardiac function [ 39 , 40 ]. Hence, the rats at 12 weeks of HFD are on a one-way road towards lipid-induced cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…25 In autoimmune myocarditis, miR-141-3p alleviates myocardial inflammatory reactions by targeting STAT4. 26 In our previous study, miR-141-3p had an effect on myocardial hypertrophy and fibrosis induced by low-dose PA. 17 The results of the present study revealed that PA-induced myocardial lipotoxic injury was increased after overexpression of miR-141-3p, whereas downregulation of miR-141-3p expression alleviated myocardial lipotoxic injury. These results highlight a potentially novel therapeutic target for future methods of intervention in saturated fatty acid (SFA)-induced myocardial injury.…”
Section: Discussionmentioning
confidence: 46%
“…miR-141-3p expression was found to be upregulated in PA-induced H9c2 cells, in agreement with our previous study in HFD-induced obese rats. 17 TGF-β1. 25 In autoimmune myocarditis, miR-141-3p alleviates myocardial inflammatory reactions by targeting STAT4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-148a-3p significantly up-regulates the expression levels of PPARγ , C/EBPα , and FABP4 , thereby promoting intracellular triglyceride accumulation [ 12 ]. Moreover, studies in animals model and humans also showed that many miRNAs play positive or negative functions in adipose tissue, including regulating the differentiation of adipocyte, metabolic, and endocrine functions [ 13 , 14 ]. Diet-induced fat in rabbits has a similar lipid metabolism to humans, making rabbits a reliable and low-cost obesity research model [ 15 ].…”
Section: Introductionmentioning
confidence: 99%